2011
DOI: 10.1007/s00198-011-1762-3
|View full text |Cite
|
Sign up to set email alerts
|

Is vascular calcification associated with bone mineral density and osteoporotic fractures in ambulatory, elderly women?

Abstract: Osteoporosis and aortic calcification appear to be independent processes in a cohort of ambulatory, elderly women. However, potential confounding factors may be present and prospective studies are needed to investigate this situation further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
(27 reference statements)
2
17
0
Order By: Relevance
“…In 340 women, severe mitral annular calcification was associated with higher prevalence of osteoporosis diagnosed by DXA (40). By contrast, several studies show that, after adjustment for age and other confounders, the association between BMD and coronary artery calcification is not significant (27,35,41,42).…”
Section: Vascular Calcification and Fracture Riskmentioning
confidence: 94%
See 1 more Smart Citation
“…In 340 women, severe mitral annular calcification was associated with higher prevalence of osteoporosis diagnosed by DXA (40). By contrast, several studies show that, after adjustment for age and other confounders, the association between BMD and coronary artery calcification is not significant (27,35,41,42).…”
Section: Vascular Calcification and Fracture Riskmentioning
confidence: 94%
“…Aortic calcification is a dynamic process and its severity at a given moment may not predict its long term progression (32,33). Wang et al and Flipon et al found no association between AAC and risk of non-vertebral fracture in elderly women (34,35). However, AAC threshold was low.…”
Section: Vascular Calcification and Fracture Riskmentioning
confidence: 97%
“…While some of them have reported an increased fracture risk with increased vascular calcification [14,17], other studies have not found such results [11,18].…”
Section: Introductionmentioning
confidence: 97%
“…It has motivated several investigators to evaluate whether bone mineral density (BMD) and vascular calcification (VC) in several vascular beds are associated beyond the aging process and independent of potential confounders [8e14]. Among studies with a cross-sectional design, an inverse relation between aortic or coronary artery calcification (CAC) and BMD has been reported by some [8,9] but not others [10,11]. In contrast, longitudinal studies have consistently shown that increased BMD loss is associated with increased aortic vascular calcification assessed through different imaging modalities, such as X-rays and radiogrammetry [12,13] as well as through computed tomography [14], this relation has not been explained by aging and other shared risk factors and has been found mainly in women.…”
Section: Introductionmentioning
confidence: 99%
“…However, the adjustment for the measures of general health and frailty had a limited impact on these associations. Some, 1,4,5 but not all, 2,29,30 prospective studies showed that severe AAC is associated with higher risk of fragility fracture. This association was found both in men and in women, for various types of fracture (hip, vertebra, all osteoporotic fractures) and remained significant after adjustment for BMD.…”
Section: Association Between the Prevalent Cardiovascular Pathology Amentioning
confidence: 99%